Module development and determination of its effectiveness through different media techniques in slide tape presentation - Sy, Lolita L. (1984)
This study attempts to contribute towards a balanced orientation on caring. This is a module of instruction which used media and different media methods. Subjects of the study were thirty senior nursing students of the University of the East College of Nursing. They were exposed to projected media in the classroom setting. A pretest and a posttest along with five discussion questions were used. On the basis of the investigation, it was concluded that media does teach regardless of the utilization of media technique or absence of media technique. However, the findings in this study are not conclusive because a one-shot study is hardly reliable to determine the effects of the treatment in learning.